Empowerment of Coastal Communities in Early Handling of Emergencies for Drowning Victims : Pemberdayaan Masyarakat Pesisir Dalam Penanganan Awal Kegawatdaruratan Pada Korban Tenggelam (JURNAL UNEJ, 2023)
While drowning is one of the most common causes of unintentional injury-related morbidity and mortality worldwide, drowning remains a significant public health problem. Drowning has become a neglected health problem, primarily not emerging from global development and health discourse, so the UN passed its first resolution related to global drowning prevention in 2021. This community service aims to improve the cognitive function of fishermen and coastal communities through primary life support education and counseling. (BHD) in communities at risk of experiencing emergency cases in Batu Be Lubang Village, Central Bangka Regency. The method used in implementing health promotion activities is lectures and basic life support simulations to improve people's cognitive function.